The association of ideal cardiovascular health with self-reported health, diabetes, and adiposity in African American males - Emmanuela B. Aboagye-Mensah; Rosevine A. Azap; James B. Odei; Darrell M. Gray, II; Timiya S. Nolan; Rana Elgazzar; DeVeonne White; John Gregory; Joshua J. Joseph (Preventive Medicine Reports, 2020)
African American (AA) men have the highest age-adjusted all-cause mortality rate in the United States of America (US) and a high burden of cardiovascular risk factors. The African American Male Wellness Walk (AAMWW) seeks to reduce such health disparities among AA males. The association of a combination of ideal cardiovascular health (ICH) metrics (blood pressure, glucose, cholesterol, body mass index (BMI), physical activity, and smoking) with self-reported health, diabetes, and body fat percentage was examined among 729 AA male participants from the 2017 and 2018 AAMWWs. Six metrics of ICH were categorized into a three-tiered ICH score 0–2, 3–4, 5–6. Linear and logistic regression modeling was performed with adjustment for age and insurance. Seven percent of men attained 5–6 ICH metrics at baseline. Participants with 5–6 ICH metrics versus 0–2 had 256% higher odds of excellent self-reported health compared to good, fair or poor (p < 0.0001). After exclusion of glucose from the ideal cardiovascular health score, participants with 3–4 versus 0–2 ICH metrics had a 48% lower odds of diabetes (p < 0.0031). After exclusion of BMI from the ICH score, participants with 5 ICH metrics had a 14.1% lower body fat percentage versus participants with 0–2 ICH metrics (p = 0.0057). Attainment of higher ideal cardiovascular health scores is associated with higher odds of self-reported health, lower odds of diabetes and lower body fat percentage among AA men. Future strategies leading to greater attainment of cardiovascular health in AA males will be important to advance health equity.